Zrcalo življenja ali njegov vzor - Virant, Špela (Primerjalna književnost, 2014)
This article uses the example of ahistorical twentieth-century realism to demonstrate how the hypothesis about universal, ahistorical functions of literature in relation to non-literary reality can contribute to in-depth historical treatment of literary phenomena.
Keywords: Lukács, György, 1885-1971; literarne smeri; realizem; novi realizem; funkcije literature; ahistoričnost; univerzalnost